Map of Manitoba showing areas populated by Indians and Metis - Community Welfare Planning Council (Winnipeg, Man.) (1968)
This is a base map of Manitoba in 1968 showing the geographic distribution of Indians and Metis in the province, and also providing statistical data on population by reserve or community. [Scale 1:2,300,000]. Shows Indian reserves and communities, Metis communities, rivers, lakes, railways, roads, cities and towns. Includes list of Indian reserves/communities/tribes, Metis communities, statistical data on population (local, total and combined Indian/Metis) and number of reserves. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .